The mental health impacts of climate change: Findings from a Pacific Island atoll nation. (June 2020) - Gibson, K.E.; Barnett, J.; Haslam, N.; Kaplan, I.
Abstract: Background: Climate change is anticipated to have profound effects on mental health, particularly among populations that are simultaneously ecologically and economically vulnerable to its impacts. Various pathways through which climate change can impact mental health have been theorised, but the impacts themselves remain understudied. Purpose: In this article we applied psychological methods to examine if climate change is affecting individuals' mental health in the Small Island Developing State of Tuvalu, a Pacific Island nation regarded as exceptionally vulnerable to climate change. We determined the presence of psychological distress and associated impairment attributed to two categories of climate change-related stressors in particular: 1) local environmental impacts caused or exacerbated by climate change, and 2) hearing about global climate change and contemplating its future implications. Methods: The findings draw on data collected in a mixed-method study involving 100 Tuvaluan participants. Data were collected via face-to-face structured interviews that lasted 45 min on average and were subjected to descriptive, correlational, and between-group analyses. Results: The findings revealed participants' experiences of distress in relation to both types of stressor, and demonstrated that a high proportion of participants are experiencing psychological distress at levels that reportedly cause them impairment in one or more areas of daily life. Conclusions: The findings lend weight to the claim that climate change represents a risk to mental health and obliges decision-makers to consider these risks when conceptualizing climate-related harms or tallying the costs of inaction.